Larval stages of Areopaguristes japonicus (Miyake, 1961) (Decapoda: Anomura: Diogenidae) described from laboratory reared material - Lee, Seok Hyun; Ko, Hyun Sook (Zootaxa, 2012)
Areopaguristes japonicus (Miyake, 1961) is recorded from South Korean waters for the first time with the collection of an ovigerous female. The zoeal and megalopal stages of this species are described from laboratory reared material and compared to larvae of eight other described Diogenidae species from the northwestern Pacific. The larvae of A. japonicas are distinguished from those of other diogenids by mediodorsal spines on zoeal pleomeres 3 and 4 and having a spine on the mediodorsal margin of the megalopal pleomere 2. A provisional key for identifying diogenid zoeas from the northwestern Pacific is provided.